Sosialisasi Bahaya Adiksi Internet Bagi Anak dan Remaja di SMA Negeri 4 Pematangsiantar - Tiarma Intan Marpaung; Asima Rohana Sinaga; Melda Veby Ristella Munthe; Firinta Togatorop; David Togi Hutahaean (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Internet addiction is becoming one of the worrying phenomena for Indonesian teenagers. The internet has an impact on our lives, both positive and negative. The positive impact of the Internet includes helping children learn to explore, cognitively train, relieve tension or provide entertainment, and. affiliated with peers. While the negative impact that can occur when using the internet excessively is disrupting family life, work, education, sleep, hobbies, and social relationships. The most common threat when a person is addicted is his or her inability to regulate emotions. A person will more often feel feelings of sadness, loneliness, anger, shame, fear to go out, be in situations of high family conflict, and have low self-confidence. These results in children and adolescents can become introverted and indifferent to the surrounding environment, thus affecting their social life, such as relationships with peers or family. It is likely that it can plunge children and adolescents who are addicted to the internet into criminal acts, both in the real world and cyberspace.